17β-Estradiol Promotes Schwann Cell Proliferation and Differentiation, Accelerating Early Remyelination in a Mouse Peripheral Nerve Injury Model. (30th October 2016) - Chen, Yan; Guo, Wenjie; Xu, Liangzhi; Li, Wenjuan; Cheng, Meng; Hu, Ying; Xu, Wenming
Abstract : Estrogen induces oligodendrocyte remyelination in response to demyelination in the central nervous system. Our objective was to determine the effects of 17β -estradiol (E2) on Schwann cell function and peripheral nerve remyelination after injury. Adult male C57BL/6J mice were used to prepare the sciatic nerve transection injury model and were randomly categorized into control and E2 groups. To study myelination in vitro, dorsal root ganglion (DRG) explant culture was prepared using 13.5-day-old mouse embryos. Primary Schwann cells were isolated from the sciatic nerves of 1- to 3-day-old Sprague–Dawley rats. Immunostaining for myelin basic protein (MBP) expression and toluidine blue staining for myelin sheaths demonstrated that E2 treatment accelerates early remyelination in the "nerve bridge" region between the proximal and distal stumps of the transection injury site in the mouse sciatic nerve. The 5-bromo-2′-deoxyuridine incorporation assay revealed that E2 promotes Schwann cell proliferation in the bridge region and in the primary culture, which is blocked using AKT inhibitor MK2206. The in vitro myelination in the DRG explant culture determined showed that the MBP expression in the E2-treated group is higher than that in the control group. These results show that E2 promotes Schwann cell proliferation and myelination depending on AKT activation.